Electrochemical Corrosion Behavior of High Velocity Oxy-Fuel (HVOF) Superalloy Coatings On Ductile Irons - Yusuf Kayalı; Aysel Büyüksağiş; Şükrü Talaş; Muhammet Karabaş; Yılmaz Yalçın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, alloyed and unalloyed ductile irons(DI) were coated with two different Ni-based superalloy materials by HVOFmethod. Microstructure and phase analyzes of the coatings were performed byusing SEM, EDX, XRD methods. Theelectrochemical corrosion behavior of alloyed and unalloyed DI is investigatedin 3.5% (w / v) NaCl solution. As a result of the characterization studies, itwas observed that a dense non-porous coating layer of about 80 μm thickness wasobtained on the cast iron samples and continuous adhesion was provided betweenthe coating and the substrate. It has been determined that the cast iron coatedwith AMDRY 9624 contains γ and β intermetallic phases and the coating producedwith AMDRY 9951 commercial powder contains only γ phase. As a result of coatingprocess, the corrosion rate of the alloyed and unalloyed spherical graphitecast irons is reduced. Also, the corrosion rate of the coating produced withAMDRY 9951 is higher than the coating produced with AMDRY 9624. The presence ofintermetallic phases in the coating produced with AMDRY 9624 increased thecorrosion resistance of the coatings.